‘The silent Arachnes that weave unrestingly in our Imagination’: The Industrial Metaphoric Web in Thomas Carlyle’s Sartor Resartus - Marie Laniel (Cahiers Victoriens et Edouardiens)
One of the staunchest critics of the ‘Age of Machinery’, who repeatedly condemned the spiritual degradation induced by the submission of men to machines, Thomas Carlyle was also fully aware of the interpretive challenges posed to the social critic by the perpetual metamorphoses of industrial society. In Book I, chapter 10 of Sartor Resartus (1833–34), Thomas Carlyle revisits the myth of Arachne and adapts Ovid’s tale to the industrial context: ‘Shall we tremble before clothwebs and cobwebs, whether woven in Arkwright looms, or by the silent Arachnes that weave unrestingly in our Imagination?’ Carlyle’s modern-day Arachnes epitomize the painful changes experienced by factory workers, and their incessant spinning and weaving in the factory of the mind reflects the contamination of inner life by the rhythms of machinery. However, because they connect the realm of matter and the realm of poetry, Carlyle’s Arachnes also epitomize the workings of imagination, the transformative power of poetic language in the face of change and the capacity of ‘symbolic systems’ to ‘make’ and ‘remake’ the world—to quote Paul Ricœur’s The Rule of Metaphor. The web they spin materialises the ‘tensional’ quality of metaphoric truth, the ‘tensive aliveness’ of the metaphoric process.